HETEROSIS IN RELATION TO COMBINING ABILITY IN HYBRIDS BETWEEN MULTIVOLTINE AND BIVOLTINE BREEDS OF THE SILKWORM, BOMBYX MORI L. - CHOUDHARY, NAZIA; SINGH, AVINDRA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
Combining ability and hybrid vigour analysis for twelve economic characters was carried out in hybrids between multivoltine and bivoltine silkworm breeds of the silkworm, Bombyx mori L. General combining ability (GCA) effects revealed that among the lines. 96H was found good general combiner exhibiting significant GCA effects for eight characters. Among testers. CSR2 and CSR4 were found good combiners exhibiting significant GCA effects for seven characters each. Out of thirty-one multivoltine N bivoltine hybrids, two hybrids viz. 96AX NB4D2 and 96E X CSR3 showed their superiority by manifesting significant specific combining ability (SCA) effects for four characters each. Five hybrids viz. BL67 N CSR2. BL67 N NB4D2, 96A X CSR4. 96E X CSR2 and 96H X CSR 17 manifested maximum hybrid vigour for seven characters followed by two hybrids namely BL67 N CSR3. BL67 N CSR4 that manifested significant hybrid vigour for six characters each.